Diagnostični in terapevtski posegi na biliarnem traktu - Mlinarič, Vladimir (Endoskopska revija, 2006)
Several noninvasive diagnostic techniques, including contrast-enhanced two-phase spiral CT, 3D ultrasound, and, the most important MR cholangiopancreatography, have been widely adopted in the recent years. Despite their high sensitivity and specificity rates, they have not yet replaced endoscopic retrograde cholangiography (ERCP), which remains the gold standard procedure in the diagnosis of biliary tract pathology. The algorithm for differential diagnosis involves the use of oesophagogastroduodenoscopy (EDGS) and endoscopic ultrasound in specific cases. EDGS is used to assess patency of the upper digestive tract, and to detect primary pathological changes and consequences of the diseases affecting the gallbladder, bile ductsor pancreas (malignant overgrowth, fistula formation, ulceration). Endoscopic ultrasound provides the most accurate information about ampullary and periampullary lesions, and changes in the common bile duct, gallbladder, and the adjacent great vessels and lymph nodes. ERCP done with other endoscopic surgical procedures, such as endoscopic papillotomy (ETP), electroresection of the ampulla of Vater, lithotripsy, retrieval of calculi and foreign bodies, dilatation of strictures and endoscopic bile drainage (stenting and nasobiliary tube placement), remains an irreplacable tool in thetreatment of biliary tract diseases. When choosing the most appropriate approach to diagnosis and treatment of gallbladder and bile duct diseases one should consider the scope and limitations of individual techniques and their role in the complementary treatment of these diseases (endoscopy-surgery, interventional radiology and conventional and laparoscopic surgery).
Keywords: Biliary Tract Surgery; Endoskopija prebavil; Endosonografija; Endoscopy, Digestive System; Endosonography; Holangiopankreatografija endoskopska, retrogradna; Cholangiopancreatography, Endoscopic Retrograde; Žolčni kamni; Cholelithiasis; Holangitis; Holedohus, kamni; Common Bile Duct Calculi; Holestaza; Vater'S Ampulla; Jetra, presaditev; Cholangitis; Pancreatitis; Pankreatitis; Papila Vateri; Cholestasis; Liver Transplantation; prebavila; žolčnik; diagnostika; trebušna slinavka; žolčevod; zdravljenje; therapy; metode; endoscopy; endoskopija